Squared Plus Squared Is Squared

Algebra Level 2

( 2 x 1 ) 2 + 4 ( x + 3 ) 2 = ( 2 x + 7 ) 2 (2x - 1)^2 + 4(x + 3)^2 = (2x + 7)^2

Solve for x x in the set of real numbers.

x = 1 x = -1 x = 3 x = 3 None of the choices x = 1 , 3 x = -1,3

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Michael Huang
Apr 11, 2017

This solution looks into some mathematical approaches - geometric and algebraic.


Geometric Approach


Recall that the Pythagorean Theorem is a 2 + b 2 = c 2 a^2 + b^2 = c^2 where a a and b b are side lengths of the triangle, and c c is the hypotenuse.

The given equation can be expressed as ( 2 x 1 ) 2 + ( 2 ( x + 3 ) ) 2 = ( 2 x + 7 ) 2 (2x - 1)^2 + \left(2(x + 3)\right)^2 = (2x + 7)^2

Looking at each of the squared terms individually, we can see that the equation resembles the Pythagorean Theorem. In this case, we can relate this to the triangle of side lengths ( 2 x 1 ) (2x - 1) , 2 ( x + 3 ) 2(x + 3) and ( 2 x + 7 ) (2x + 7) , where ( 2 x + 7 ) (2x + 7) is the longest side of the triangle aka the hypotenuse. Here is the following illustration:

Note: For the solution, we allow the right triangle in the Cartesian plane, so we don't neglect triangles with negative side lengths. Otherwise, the solutions are not complete.

Let y = 2 x 1 y = 2x - 1 , so the new equation is y 2 + ( y + 7 ) 2 = ( y + 8 ) 2 y^2 + (y + 7)^2 = (y + 8)^2

Visually, 5 5 - 12 12 - 13 13 satisfies the given property, where y = 5 y = 5 . Considering negative numbers of y y , y = 3 y = -3 (which gives 3 3 - 4 4 - 5 5 ) must also work!

Thus, x = 1 , 3 \boxed{x = -1, 3} . By noticing the side length differences, the method turns out to be very nice and elegant. :)

It is also possible, but not necessary (and possibly not rigorous!), to transform this problem into the system of equations. Set a = y a = y , b = y + 7 b = y + 7 and c = y + 8 c = y + 8 , so a + b = 7 a + c = 8 b + c = 1 \begin{array}{rl} -a + b &= 7\\ -a + c &= 8\\ -b + c &= 1 \end{array} where the triplets are 3 4 5 3-4-5 and 5 12 13 5-12-13 .


Algebraic Approach


From the previous approach, we simplified into smaller coefficients in the equation, which can easily be solved algebraically. The resulting equation after combining like terms is y 2 2 y 15 = 0 y^2 - 2y - 15 = 0

We can also solve for x x without having to perform the variable substitution. These methods are all great to solve the problem. :)

( 2 x 1 ) 2 + 4 ( x + 3 ) 2 = ( 2 x + 7 ) 2 (2x-1)^2+4(x+3)^2=(2x+7)^2

Expand and combine like terms.

4 x 2 4 x + 1 + 4 ( x 2 + 6 x + 9 ) = 4 x 2 + 28 x + 49 4x^2-4x+1+4(x^2+6x+9)=4x^2+28x+49

4 x + 1 + 4 x 2 + 24 x + 36 = 28 x + 49 -4x+1+4x^2+24x+36=28x+49

4 x 2 + 24 x 4 x 28 x + 1 + 36 49 = 0 4x^2+24x-4x-28x+1+36-49=0

4 x 2 8 x 12 = 0 4x^2-8x-12=0

x 2 2 x 3 = 0 x^2-2x-3=0

By factoring, we have

( x 3 ) ( x + 1 ) = 0 (x-3)(x+1)=0

x = 3 x=3

x = 1 x=-1

Check by substituting:

when x = 3 x=3

( 2 x 1 ) 2 + 4 ( x + 3 ) 2 = ( 2 x + 7 ) 2 (2x-1)^2+4(x+3)^2=(2x+7)^2

[ 2 ( 3 ) 1 ] 2 + 4 ( 3 + 3 ) 2 = [ 2 ( 3 ) + 7 ] 2 [2(3)-1]^2+4(3+3)^2=[2(3)+7]^2

25 + 144 = 169 25+144=169

169 = 169 169=169 (true)

when x = 1 x=-1

( 2 x 1 ) 2 + 4 ( x + 3 ) 2 = ( 2 x + 7 ) 2 (2x-1)^2+4(x+3)^2=(2x+7)^2

[ 2 ( 1 ) 1 ] 2 + 4 ( 1 + 3 ) 2 = [ 2 ( 1 ) + 7 ] 2 [2(-1)-1]^2+4(-1+3)^2=[2(-1)+7]^2

9 + 16 = 25 9+16=25

25 = 25 25=25 (true)

\therefore The solutions are 3 \boxed{3} and 1 \boxed{-1} .

There is another approach for this problem. Can you find one? :)

Michael Huang - 4 years, 2 months ago

Log in to reply

just check each answer on this multiple choice problem -_-

Razzi Masroor - 4 years, 1 month ago

Log in to reply

maybe someone should fix that

Razzi Masroor - 4 years, 1 month ago

as an european, i thought the 3rd answer was -1.3 because we use the "," as a "."

maxime weill - 4 years, 1 month ago

Can be solved easier with difference of square. You move the first Sq on the left to the right side of the equation. It becomes a simple 2nd degree equation. Factor it out as (×-3)(x+1)=0

w oba - 3 years, 12 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...